2021
DOI: 10.1080/09298215.2021.1978506
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance in violin bowing: Effects of attentional focus on acoustical, physiological and physical parameters of a sound-producing action

Abstract: Violin bowing is a specialised sound-producing action, which may be affected by psychological performance techniques. In sport, attentional focus impacts motor performance, but limited evidence for this exists in music. We investigated effects of attentional focus on acoustical, physiological, and physical parameters of violin bowing in experienced and novice violinists. Attentional focus significantly affected spectral centroid, bow contact point consistency, shoulder muscle activity, and novices' violin sway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 60 publications
(105 reference statements)
2
16
0
Order By: Relevance
“…However, we found no significant difference in errors between the internal and external foci, suggesting that for this task, a focus on sound was not a beneficial alternative to an internal focus. This finding is in line with our results from a previous study on FOA in a different task of open string bowing ( Allingham et al, 2021, in review ) in which we similarly found that a somatic focus increased spectral centroid of violin tone and reduced shoulder muscle activity compared to internal focus but that there were no significant differences between the internal and distal external foci.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we found no significant difference in errors between the internal and external foci, suggesting that for this task, a focus on sound was not a beneficial alternative to an internal focus. This finding is in line with our results from a previous study on FOA in a different task of open string bowing ( Allingham et al, 2021, in review ) in which we similarly found that a somatic focus increased spectral centroid of violin tone and reduced shoulder muscle activity compared to internal focus but that there were no significant differences between the internal and distal external foci.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study in a violin tone-production task, we found that an FOA on tactile feedback increased tone brightness, reduced shoulder muscle activity, and increased novices’ violin sway relative to an arm movement focus while improving consistency of bow-bridge distance relative to a sound focus ( Allingham et al, 2021, in review ). These results suggest benefits of a focus on tactile feedback in violin open-string tone production.…”
Section: Related Literaturementioning
confidence: 84%
See 1 more Smart Citation
“…Body movements thus actively tune the metrical framework through which we attend to music (Large et al, 2015;Kozak, 2021). In violinists, the link between body kinematics and focus of attention has been demonstrated as well (Allingham et al, 2021). More particularly, shifts in head motion patterns during perturbation of solo string players have been interpreted as reflecting attentional changes (Visi et al, 2014;Rozé et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The solution to this contradiction could be to abandon the binary view of attentional focus (i.e., external vs. internal): as Allingham et al (2021) argue, the simplicity of this understanding might not be appropriate to fully capture the complex procedure associated with playing an instrument: additional factors, such as the auditory feedback, musicality, emotions, and the felt resonations of the created sounds might complicate this equation. Therefore, they introduced an additional focus condition into their study on violin bowing (Allingham et al, 2021): a somatic focus, targeting the sensations resulting from the interaction with the instrument (i.e., resonance) within the body, and found that this condition was superior to both internal and external conditions in terms of movement effectiveness. A memoir of a recovered trombonist (Chopyk, 2021) reinforces the benefits of this "somatic" focus: they achieved the best rehabilitation results by turning their attention toward the air resonating inside their wind instrument.…”
Section: Focus Habits and Nomenclaturementioning
confidence: 99%